Influence of Blood Flow Restriction in the Early Phase After Anterior Cruciate Ligament Reconstruction with Hamstring Graft: Proposal for a Randomized Multicentric Experimental Protocol (International Journal of Physiotherapy, 2021)
Background: The rupture of the anterior cruciate ligament is a recurrent injury, especially in athletes (70%), and surgery is often preferred. However, a consequent post-surgical quadricipital atrophy is commonly noticed. Here, we present a research project proposing early quadricipital muscle strengthening under Blood Flow Restriction (BFR) in postsurgery patients. The objectives are to assess the impact of early post-surgical muscle strengthening under BFR on quadricipital strength and spatio-temporal parameters during gait analysis.Methods: A prospective, interventional, experimental, and multi-center study is proposed comparing a control group benefiting from muscle strengthening alone to an experimental group benefiting from muscle strengthening under BFR. The protocol was carried out between D3 and D31 post-surgery on a sports population.Results: We expect this study to provide an additional therapeutic option in the anterior cruciate ligament's immediate and early post-operative protocols in athletes.Conclusion: This study project aims to offer innovative and efficient rehabilitation that answers the athlete’s needs andaligns with an evidence-based practice approach.